Determinantes de necesidades insatisfechas y descontinuación de métodos anticonceptivos modernos en mujeres en edad fértil de Iquitos metropolitano 2024 - Tello Dávila, Sergio Arturo (2025)
Introduction: Modern contraceptive methods (MACs) are identified as effective methods to control fertility and promote slow population growth, promoting access to modern MACs among women of reproductive age (15-49 years) proves to be an efficient public health intervention to improve maternal and child health. However, barriers persist that limit their effective and continuous access. Objective: To determine the association between determinants of unmet need and discontinuation of modern contraceptive methods among women attended in an Iquitos Hospital, 2024. Population: The population was women of childbearing age, between 15 and 49 years, attending the “Family Planning” program of the Regional Hospital of Loreto, during the months of August to November 2024, the sample consisted of 384 participants. Methodology: The research was descriptive, qualitative, observational and cross-sectional. Results: A total of 384 female participants were surveyed, within the sociodemographic and economic factors it was identified that the average age was 28.5 years, 57.03% were single and 51.56% had high school education. Regarding obstetric factors, the average number of live children of these women was 2.8, the average number of sexual partners was 1.5 and the average inter-gestational period (IGP) was 3.8 years. Bivariate analysis showed that partner opposition to MAC use (p=0.03 <0.05, OR=1.120) and difficulty with MAC access (p=0.01<0.05, OR=1.155) have a relationship associated with beliefs and rumors in the environment about health risks of MACs as determinants of unmet needs; further that, partner opposition to MAC use (p=0.05≈0.05, OR=1. 093), lack of information about MAC (p=0.05≈0.05, OR=1.260) and difficulty with access to MAC (p=0.03<0.05, OR=1.057) have an associated relationship with experiencing side effects and lack of informationabout warning signs when using MAC as determinants of unmet need. Conclusion: It was determined that there is no statistically significant association between unmet need factors and discontinuation of MAC in women of childbearing age attended in a hospital in Iquitos.